Molecular characterization of circulating respiratory syncytial virus (RSV) genotypes in Gilgit Baltistan Province of Pakistan during 2011-2012 winter season. - Uzma Bashir; Muhammad Masroor Alam; Hajra Sadia; Syed Sohail Zahoor Zaidi; Birjees Mazher Kazi (PLoS ONE, 2013)
Respiratory syncytial virus (RSV) is the major cause of acute lower respiratory tract infections in young children, but very little is known about its epidemiology and circulating genotypes in Pakistan. This study analyzed the epidemiological and molecular characteristics of RSV genotypes detected in Pakistani children less than 2 years of age with acute respiratory tract infections (ARIs) in a tertiary care hospital in Gilgit Baltistan (GB) province during 2011-12 winter season. RSV was detected in 75 out of 105 children presenting with acute respiratory infection. Male infants between 2-6 months age made up the highest percentage of RSV positive cases. Epidemiological factors such as pre-maturity, mean weight, clinical features and diagnosis when compared between RSV positive and negative groups were found to be statistically insignificant. Phylogenetic analysis classified all 75 of the RSV strains into 71 strains of subgroups A and 4 strains of subgroup B, respectively. Strains belonging to subgroups A and B were further subdivided into NA1/GA2 and BA, respectively. The nucleotide and deduced amino acid sequence identities were relatively high among these strains (>90%). Both RSV-A and RSV-B isolates had two potential N-glycosylation sites in HVR2 of G protein and with heavy O-glycosylation of serine and threonine residues (G scores of 0.5-0.7). This report highlights the significance of RSV as a dominant viral etiologic agent of pediatric ARIs, and need for continued molecular epidemiological surveys for early detection of prevalent strains and newly emerging genotypes to understand epidemiology of RSV infections in various regions of Pakistan.